2022
DOI: 10.1002/ijc.34346
|View full text |Cite
|
Sign up to set email alerts
|

Extensive‐stage small‐cell lung cancer: Current management and future directions

Abstract: Extensive-stage small-cell lung cancer (ES-SCLC) is regarded as a refractory carcinoma associated with extremely rapid disease progression. After more than three decades without clinical advances, research on immune checkpoint inhibitors (ICIs) combined with platinum-based chemotherapy has led to the first treatment breakthrough, establishing a new standard for the first-line treatment of ES-SCLC. Further studies have extensively evaluated small-molecule antiangiogenic drugs, PARP inhibitors, as well as lurbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Given the small sample size of this study, our conclusions need to be further validated in a larger cohort. To date, there has been no breakthrough in the search for effective biomarkers to select advantaged patients, and the initial framework for molecular subtypes of SCLC is not yet mature [27] . To clarify the dominant population of single immunotherapy and combined immunotherapy, the best opportunity for immunotherapy, and the ideal mode of combined therapy are urgent problems to be solved in the next research.…”
Section: Discussionmentioning
confidence: 99%
“…Given the small sample size of this study, our conclusions need to be further validated in a larger cohort. To date, there has been no breakthrough in the search for effective biomarkers to select advantaged patients, and the initial framework for molecular subtypes of SCLC is not yet mature [27] . To clarify the dominant population of single immunotherapy and combined immunotherapy, the best opportunity for immunotherapy, and the ideal mode of combined therapy are urgent problems to be solved in the next research.…”
Section: Discussionmentioning
confidence: 99%
“… 141 Over 60% of patients with SCLC are diagnosed with extensive-stage SCLC, facing a median survival of less than 10 months. 142 Even for those diagnosed with limited-stage SCLC, survival rates are generally poor. While initial responses to standard chemotherapy and radiotherapy are common, rapid relapse due to acquired chemotherapy resistance is a frequent challenge.…”
Section: The Notch Signaling Pathway and Cancermentioning
confidence: 99%
“…With the publication of results from the IMpower133, CASPIAN, ASTRUM-005, and CAPSTONE-1 studies, ICIs have been shown to greatly improve the survival of patients with ES-SCLC [42]. Although immunotherapy combined with chemotherapy (ICT) plays a signi cant role in ES-SCLC, data related to the combined e cacy and safety of RT is insu cient, and the results are controversial.…”
Section: Earlier Initiation Of Rit In Es-sclc Leads To Improved Survi...mentioning
confidence: 99%